2020
DOI: 10.1021/acs.analchem.9b03626
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Accessibility for Characterizing Microplastics: Introducing New Application-Based and Spectral Libraries of Plastic Particles (SLoPP and SLoPP-E)

Abstract: As smaller particle sizes are increasingly included in microplastic research, it is critical to chemically characterize microparticles to identify whether particles are indeed microplastics. To increase the accessibility of methods for characterizing microparticles via Raman spectroscopy, we created an application-based library of Raman spectroscopy parameters specific to microplastics based on color, morphology, and size. We also created two spectral libraries that are representative of microplastics found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 211 publications
(113 citation statements)
references
References 34 publications
0
113
0
Order By: Relevance
“…Parameters for spectral acquisition were determined using the application-based library. 53 Manual baseline correction and smoothing of Raman spectra was performed in LabSpec6 if necessary. Raman spectra were matched using Bio-Rad KnowItAll software with associated reference libraries and the SLoPP/SLoPP-E Raman libraries created at the University of Toronto.…”
Section: Case Studymentioning
confidence: 99%
“…Parameters for spectral acquisition were determined using the application-based library. 53 Manual baseline correction and smoothing of Raman spectra was performed in LabSpec6 if necessary. Raman spectra were matched using Bio-Rad KnowItAll software with associated reference libraries and the SLoPP/SLoPP-E Raman libraries created at the University of Toronto.…”
Section: Case Studymentioning
confidence: 99%
“…Spectra were sent to Bio-Rad KnowItAll software to assign spectral matches with reference spectra using KnowItAll Raman Spectral Library, as well as databases consisting of reference plastic polymers and environmentally aged MPs created in our lab. 22 The Bio-Rad KnowItAll and ID Expert spectral matching software applies corrections to the spectra automatically (baseline, vertical clipping, intensity distortion, horizontal offset, vertical offset, Raman intensity distortion). Spectral matches are assigned based on visual confirmation for similar peak alignment and intensity, as well as Hit Quality Index (HQI) score as calculated by the Bio-Rad KnowItAll and ID Expert matching algorithm.…”
Section: Part 1: Testing An Adhesivementioning
confidence: 99%
“…Additionally, in this study we chemically identified all particles from the faecal precursor samples using micro-Raman spectroscopy, which allowed us to exclude potentially natural particles from our analyses. Forty-four percent of the initial particles found on the filters were natural or unknown, highlighting the importance of particle identification to reduce overestimations of anthropogenic particles, especially when dealing with small particle sizes (Lenz et al, 2015;Munno et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Chemically identifying and characterizing particles is becoming an increasingly crucial step in order to ensure particles are in fact plastic or of anthropogenic origin, and to avoid overestimating counts of anthropogenic particles (Lenz et al, 2015;Munno et al, 2020). This is particularly relevant as more studies are now reporting on very small particles that are impossible to positively confirm visually (Lenz et al, 2015;Munno et al, 2020). Particle identification and characterization is most commonly done through Fourier-transform infrared spectroscopy (FTIR; e.g.…”
Section: Polymer Identification Techniquesmentioning
confidence: 99%
See 1 more Smart Citation